Facial Reanimation Utilizing Combined Orthodromic Temporalis Muscle Flap and End-to-Side Cross-Face Nerve Grafts - Viterbo, Fausto [UNESP]; Romao, Adriana [UNESP]; Brock, Ryane Schmidt; Joethy, Janna (Springer, 2014)
Individuals with facial paralysis of 6 months or more without evidence of clinical or electromyographic improvement have been successfully reanimated utilizing an orthodromic temporalis transfer in conjunction with end-to-side cross-face nerve grafts. The temporalis muscle insertion is released from the coronoid process of the mandible and sutured to a fascia lata graft that is secured distally to the commissure and paralyzed hemilip. The orthodromic transfer of the temporalis muscle overcomes the concave temporal deformity and zygomatic fullness produced by the turning down of the central third of the muscle (Gillies procedure) while yielding stronger muscle contraction and a more symmetric smile. The muscle flap is combined with cross-face sural nerve grafts utilizing end-to-side neurorrhaphies to import myelinated motor fibers to the paralyzed muscles of facial expression in the midface and perioral region. Cross-face nerve grafting provides the potential for true spontaneous facial motion. We feel that the synergy created by the combination of techniques can perhaps produce a more symmetrical and synchronized smile than either procedure in isolation.Nineteen patients underwent an orthodromic temporalis muscle flap in conjunction with cross-face (buccal-buccal with end-to-side neurorrhaphy) nerve grafts. To evaluate the symmetry of the smile, we measured the length of the two hemilips (normal and affected) using the CorelDRAW X3 software. Measurements were obtained in the pre- and postoperative period and compared for symmetry.There was significant improvement in smile symmetry in 89.5 % of patients.Orthodromic temporalis muscle transfer in conjunction with cross face nerve grafts creates a synergistic effect frequently producing an aesthetic, symmetric smile.This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors at www.spinger.com/00266.
Keywords: End-to-side neurorrhaphy; Facial palsy; Reconstructive surgical procedure; Surgical flap grafts; Temporal muscle; Orthodromic